The Effectiveness of Clarke Wright and Sequential Insertion Algorithm in Distribution Routing Aqua - Ayu Hariati; Nurul Huda Prasetya; Hendra Cipta (Pusat Studi Pengembangan Pembelajaran Matematika Sekolah UIN Sunan Kalijaga Yogyakarta Jl. Marsda Adisucipto, Yogyakarta 55281, 2021)
With the Multiple Trips condition, the results obtained for the optimal distance route that starts and stops at PT. Tirta Investama Medan with Clarke Wright Algorithm at t = 1 is 22 km and at t = t + 1 is 15.2 km. While the optimal travel distance route with the Sequential Insertion Algorithm at t = 1 is 15.05 km, and at t = t + 1 is 22.9 km. Clarke Wright Algorithm looks for an optimal solution to get the best route, while Sequential Insertion Algorithm has an excess in the election of a customer by considering customer position with available insertion track location until all customer have been assigned. The Clarke Wright Algorithm obtained a total distance of 37.2 km. In comparison, the Sequential Insertion Algorithm solution obtained a total distance of 37.95 km. It can be concluded that the route formed using the Clarke Wright Algorithm in this case is more effective than using the Sequential Insertion Algorithm.